Aksi Transformatif Inovasi Moderasi Beragama Komunitas Difabel di Kebumen - Chamidi, Agus Salim; Murtopo, Bahrun Ali (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
This research is an innovative community service research based on religious moderation with the assistance of the Directorate of Islamic Higher Education, Directorate General of Islamic Education, Ministry of Religion of the Republic of Indonesia. The research was conducted in the disabled community at the Rumah Inklusif Kebumen (RIK). The research is motivated by the diversity of people with disabilities and their families who are still vulnerable, both due to their internal and external factors. The research aims to find out changes in their critical awareness and innovative efforts in their religious moderation. The research also aims to discuss their own changes with Pierre Bourdieu's theory of social practice. The research uses a transformative action research model that emphasizes critical awareness of the disabled community, as well as social change and their reflection. The research was conducted in August-November 2021. The results showed that (1)there was critical awareness in the disabled community in the RIK to the problem of their religious moderation, and they then succeeded in building innovative goals in translating the conception of religious moderation, (2)they succeeded in making action. in their own special container called 'lumbung genuk', (3)the 'lumbung genuk' innovation contains inclusive values ​​of togetherness, brotherhood, kinship, tolerance, and caring. In the perspective of Pierre Bourdieu's social practice, the diffable community regenerates the habitus of ‘seduluran’ and ‘brayan urip’ through the granary arena with as much savings as possible. Even with this savings and loan granary strategy, they indirectly demonstrate their entrepreneurial abilities against stigma and discrimination that often arise.